Effects of genetic polymorphisms on the pharmacokinetics and pharmacodynamics of proton pump inhibitors - Zhang, He-Jian; Zhang, Xue-Hui; Liu, Jie; Sun, Lu-Ning; Shen, Yi-Wen; Zhou, Chen; Zhang, Hong-Wen; Xie, Li-Jun; Chen, Juan; Liu, Yun; Wang, Yong-Qing (Pharmacological research, 2020)
[Display omitted] Proton pump inhibitors (PPIs) are used widely for the treatment of acid-related disorders. Despite their excellent efficacy and tolerance, the pharmacodynamics and pharmacokinetics of PPIs are affected by each patient’s CYP2C19 and gastric H+,K+-ATPase genotype. The aim of this review was to analyze the effect of genetic polymorphisms on the pharmacodynamic and pharmacokinetic properties of PPIs. The gastric acid-suppressive effect of PPIs is affected by both gastric H+,K+-ATPase and CYP2C19 polymorphisms, although gastric H+,K+-ATPase polymorphisms may have larger effects. Ilaprazole and rabeprazole show relatively small differences in the pharmacokinetic and pharmacodynamic properties and clinical efficacy among the different CYP2C19 genotypes. Compared with oral administration, the intravenous infusion of PPIs is less affected by CYP2C19 polymorphism. At the same dose, each enantiomer has less variation among different CYP2C19 genotypes than a racemate mixture.